Determinants of housing supply: Case of Kuala Lumpur and Johor / Anis Nurhidayah Anuar - Anuar, Anis Nurhidayah (2007)
This study focuses on the determinants of housing supply especially in Kuala Lumpur and Johor. Many houses are being built to fulfill the customer's needs. Housing provision has played an important part of the government social policy in Malaysia. Housing as economic goods has some special characteristics that make it different from other kinds of properties. The objective of the study is to determine the factors that affect the housing supply and to examine whether there is any relationship that will exist between the factors and housing supply. The determinants of housing supply that will use in this study are house price, construction cost and interest rate. To analyze all these factors that will determine the housing supply, this study will take Kuala Lumpur and Johor as the sample population. The time horizon is from 3rd quarter of 2002 until 2nd quarter of 2006 which is five years. It will take the quarterly data. This study used multiple regressions to examine the relationship that exist between house price, construction cost and interest rate towards the housing supply. This method will determine whether independent variable has relationship or not with the dependent variable. In the previous study has said that it is so difficult to see the relationship that will exist between all the variables. Based on the study that has been conducted the result that get from this study were, there are no significant relationship between housing supply and housing price in Kuala Lumpur and Johor. There are significant relationships that exist between construction cost and gross national income with the housing supply in Kuala Lumpur and Johor.